ASSOCIATION OF DEPRESSION AND CHRONIC LOWER-BACK PAIN - Abdukadirova D.T.; Nazarova G.T.; Ruzieva O.R. (PEDAGOGS, 2025)
Abstract: In this work we aimed to study the prevalence of major depressive disorder, assess sleep quality, permanent functional disability as well as association of major depressive disorder with permanent disability, quality of life and quality of sleep in patients with chronic lower – back pain.